Comparative Analysis of Clinical Outcomes of Immediate vs. Delayed Dental Implant Placement - Muneer, Danial; Jan, Spogmay; Zaheer , Mahnoor; Khan, Alamgir; Ihrar ul Haq, Mian; Asadullah (Indus Journal of Bioscience Research, 2025)
Background: Dental implants have become the preferred method for replacing missing teeth. However, the optimal timing of implant placement remains a subject of debate. Objective: This study compares the clinical outcomes of immediate versus delayed implant placement to evaluate their success rates, complications, and patient satisfaction. Methods: This prospective observational study was conducted at Islamabad Medical and Dental College and Islamic International Dental College during July 2024 to December 2024. A total of 50 patients were added in the study. The implant was positioned with primary stability, with an insertion torque of at least 35 Ncm. If necessary, a bone graft was used to fill any gaps between the implant and the surrounding socket walls, and a resorbable membrane was placed to enhance healing. Results: The implant survival rate was 96 percent in the immediate placement group and 92 percent in the delayed placement group, with no significant difference (p = 0.56). Marginal bone loss was slightly higher in the immediate placement group (0.82 ± 0.28 mm) compared to the delayed placement group (0.75 ± 0.30 mm), but the difference was not statistically significant (p = 0.41). Soft tissue health scores were similar between the two groups (p = 0.52). Complication rates were slightly higher in the immediate placement group (16 percent) compared to the delayed placement group (12 percent), but this difference was not statistically significant (p = 0.67). Patient satisfaction scores were high in both groups, with no significant difference (p = 0.34). Conclusion: It is concluded that both immediate and delayed implant placement offer high success rates with minimal complications when proper surgical protocols are followed. Immediate placement reduces treatment duration and preserves alveolar bone but may pose a slightly higher risk of early-stage complications.